Reconstruction of Firing Techniques of Jomon Pottery Based on Firing Cloud Patterns - KOJIMA, Toshiaki; KUSE, Kenji; KOBAYASHI, Masashi; KITANO, Hiroshi (Nihon Kokogaku(Journal of the Japanese Archaeological Association), 1999)
Firing-cloud patterns left by the pottery-firing process provide critical data for reconstructing the bonfire technique of Jomon pottery. As it is difficult to observe firing-cloud patterns of Jomon pots, clarification of the process of firing-cloud pattern formation through bonfire experiments, and the accumulation of comparisons between the experimentally produced patterns and those of Jomon pots are essential. In the current contribution, based on the results of a series of experiments with open bonfires, firing-cloud patterns were classified from the process of formation as "firewood contact patterns produced by soot from wood which burns with a relatively strong flame (typically in inverted U-shapes or spots appearing in pairs), " "bar-shaped firewood contact patterns, " "contact patterns from embers, " "patterns made by soot residues, " etc. As a result of observations made with five data sets of Early and Middle Jomon pottery from eastern Japan, it was found that this classification could be applied in a great many examples, verifying that the bonfire technique had been reconstructed to a certain degree from the perspective of the process of formation of cloud patterns. From this, the following has become clear. 1. As firing-cloud patterns produced by soot from firewood which burns with a high flame were observed in many of the archaeological examples examined for this contribution, the use of open bonfires, rather than those having some kind of covering, was reconfirmed. Firing-cloud patterns from contact with firewood formed on the inside surface, and also the outside surface, of the side of the vessel which lay on the ground, and on the outside surface of the opposite side; it was accordingly clear that large amounts of firewood were placed underneath and alongside pots which were laid on their sides. On the other hand, in experiments with covered bonfires, conditions within the enclosed space approached those of kilns, and cloud patterns produced by soot from high flames were few. 2. From the observation of cloud patterns produced by contact with firewood or embers on the inside of the majority of pots in the five data sets, it is clear that fuel had been placed inside the pots. In contrast to Yayoi pottery, in which no firewood is placed within the vessel, the insertion of fuel in Jomon pots is thought to be due to the difficulty for combustible gasses to circulate otherwise, as shown in the bonfire experiments. 3. In addition to the points in common noted in observations of firing-cloud patterns in the five sets of Early and Middle Jomon pottery from eastern Japan, the following differences were also found. The Ento kaso b style vessels (especially large items) from the no. Vb peat layer of the Sannai Maruyama Site were laid horizontally on top of the firewood, with firewood and grass placed on their sides and tops; in this regard these materials differ from those of the other four sets, for which there is a high possibility that the pots were toppled into a horizontal position during firing. Conceivable reasons for using this method include (1) a deficiency in the flame reaching the rims of the vessels, if the pipe-like form of the Ento kaso b style vessels were set upright, and (2), the use of grass as fuel, in conjunction with firewood, as a means of economizing on the latter, with the large-scale production of pottery.